What to Choose Next? A Paradigm for Testing Human Sequential Decision Making - Tartaglia, Elisa M.; Clarke, Aaron M.; Herzog, Michael H. (Frontiers in Psychology, 2017)
Many of the decisions we make in our everyday lives are sequential and entail sparse rewards. While sequential decision-making has been extensively investigated in theory (e.g., by reinforcement learning models) there is no systematic experimental paradigm to test it. Here, we developed such a paradigm and investigated key components of reinforcement learning models: the eligibility trace (i.e., the memory trace of previous decision steps), the external rewards, and the ability to exploit the statistics of the environment’s structure (model-free versus model-based mechanisms). We show that the eligibility trace decays not with sheer time, but rather with the number of discrete decision steps made by the participants. We further show that, unexpectedly, neither monetary rewards nor the environment’s spatial regularity significantly modulate behavioral performance. Finally, we found that model-free learning algorithms describe human performance better than model-based algorithms.